The Determinants of Foreign Direct Investment in Somalia - Ibrahim, Mohamed Isse; Omar, Zahir Mohamed; Sheikh Ali, Ali Yassin (International Journal of Economics and Financial Issues, 2017)
This study examines determinants of foreign direct investment in Somalia, measured foreign direct investment inflow (FDI). Used time series data obtained from World Bank and SESRIC for a period of 41 years that is 1970 to 2010. Augmented Dickey-Fuller (ADF) test was used for the unit root test and ordinary Least Square statistical technique was used to assess the degree of influence the variables have on each other. The results show a negative and significant relationship in exchange rate and FDI, while, a positive and significant relationship is observed between inflation, external debt and domestic investment of FDI. Also a negative but insignificant relationship is observed between lack of government and gross domestic product FDI. Therefore, there is need for the government to retain tight monetary and fiscal policies in order to attract foreign direct investment. This study therefore recommends that central bank of Somalia should control the fluctuations of the exchange rate in order to increase the FDI. Since the inflation is higher, the study also recommends having a good government to recover the financial institutions that manage the monetary policy of Somalia. Keywords: Exchange rate, foreign direct investments, Somalia. JEL Classifications: F21, F31